A design project on fish protein concentrate (FPC) - Chu, Richard Q. (College of Engineering, 1976)
Capacity: Round scad 100 MT/day, FPC 16 MT/day -- Plant location: Navotas, Rizal -- Plant area: 72 x 45 meters -- Total capital investment: P 18,136,546 -- Annual cost of production: P 31,269,382 -- Annual sales: P 43,908,375 -- Annual income (before taxes): P 12,638,993 -- Rate of return on investment: 69% -- Payout time: 1.13 years -- Break-even point: 15% of capacity